Detection of Ancient Tombs Destruction in Mesopotamian Using Remote Sensing Data and GIS - Hasan, Ahmed Abbas; Mahameed, Ans Ibrahim; Hasan, Mariam Issam (Iraqi Journal of Science, 2026)
Geographic Information Systems (GIS) and remote sensing were used in this project to assess and monitor Umm Khashm Cemetery, one of Iraq’s most significant ancient cemeteries. Over 140,000 incidents of grave robbing were found throughout the studied area, highlighting the pervasive problem of looting. By examining soil irregularities and the shadows produced by robbed tombs, satellite imagery, including high-resolution datasets from WorldView-2 and Google Earth, was utilized to identify instances of theft. The study shows how well remote sensing and GIS work to record and evaluate cultural heritage site deterioration, offering important information for conservation initiatives. The findings highlight these technologies’ importance in safeguarding and conserving Iraq’s rich archeological legacy. Although the CORONA dataset (2.75m resolution) offered historical background, its lower resolution and greyscale imaging made it less helpful in identifying minute soil problems. Although it was constrained by spectral resolution, QuickBird (0.61 m resolution) enhanced the identification of small-scale disturbances. Using spectral analysis of soil disturbances, WorldView-2 (0.46 m resolution, multispectral) provided the best accuracy in detecting plundered tombs and differentiating between excavated and non-excavated sites. Although it lacked spectral depth, Google Earth (0.3 m resolution) was helpful for visual confirmation. WorldView-2 produced the most accurate findings, but integrating all datasets guaranteed thorough identification and verification of looting incidents.